Das Septembertestament Martin Luthers von 1522: Das Neue Testament Deutsch im Bestand des Unitätsarchivs Herrnhut - Mai, Christian (Unitas Fratrum, 2018)
With its copy of Martin Luther's 'September Testament' of 1522, his translation of the New Testament into German, the Unity Archives can count a milestone of religious, linguistic and cultural history superlatives as its own. In the assessment of the Münster church historian Albrecht Beutel, 'no other German book has ever achieved such importance'. It was a work of genius, achieved in just eleven weeks during Luther's stay in the Wartburg castle. The folio volume, first published in an initial edition of about 3,000 copies by Melchior Lotter in Wittenberg, shaped German linguistic history and was a catalyst of the Reformation. In prefaces and marginal notes Luther was able to communicate his most important insights, notably humanity's justification before God by grace and faith alone (marginal note to Romans 3). Others include the formula, in Luther's preface to the Epistle of James, 'was Christum treibet' (what advances the cause of Christ), as an expression of the essence of the Bible, and (in the Preface to the whole book) the whole New Testament as being the Gospel of God. For Luther this was a sermon whose language was formed in an intense process of engagement with the original Greek text. The Herrnhut copy is distinguished by the fact that the sermon texts have been inserted in Latin und German by an unknown hand. They show how the Bible was used in worship. The final pages were probably detached because of the much sought-after Revelation woodcuts from Cranach's studio. In the woodcut depicting the whore of Babylon she is still wearing the papal tiara, which was removed in later editions as being excessively polemical.